Aplikasi Coating Berbasis Glukomanan Porang pada Buah Apel Manalagi Potong: Application of Porang Glucomannan Based Coating on Fresh Cut Manalagi Apples - Setiawan Rusdianto, Andrew; Amilia, Winda; Puspitania, Dewi Arum (JOFE : Journal of Food Engineering, 2024)
Fresh cut apples are one of the minimally processed products that is widely marketed. However, cut apples have disadvantages because they easily experience enzymatic browning as a result of the oxidation process after the cutting process. Edible coating made from porang glucomannan can inhibit oxygen diffusion so that browning can be inhibited. The objective of this research is to determine the best porang glucomannan concentration in edible coatings on changes in brightness in fresh cut apples stored at 7℃. The research method used was an experimental method using a Completely Randomized Design (RAL). The experiment was carried out in 5 treatments ((AP0, AP1, AP2, AP3, AP4)) and 3 repetitions. The edible coating is applied using the dipping method and stored at temperature 7℃ for 3 hours. The data obtained were analyzed using one way ANOVA and continued with Duncan's Multiple Range Test (DMRT). The results of the research showed that the formulation of porang glucomannan flour in edible coating had a significant effect on the brightness of fresh cut apples. Fresh cut apples with the highest brightness are in the AP2 treatment with a value of 86.1; 85.4; 85.1; 84.7; 84.1; and 83.5 measured every 30 minutes for 3 hours when stored at 7℃.